Efektivitas Pembelajaran Daring Pada Materi Larutan Penyangga Di Kelas XI SMA Negeri 3 Kotamobagu - Pobela, Ratika; Rumondor, Dessire Adna (General Chemistry Journal, 2024)
It examines the effectiveness of online model learning on buffer solution material. This study was conducted at SMA Negeri 3 Kotamobagu in the 2021/2022 even semester. 28 class XI B students participated in this study. The research findings show that the teacher's ability to manage online learning is very effective with a score of 3.58, student activities during the online learning process are active with a score of 3.39, students' responses to the online learning model are positive with 77.5% agreeing, and students' learning outcomes through the online model completed classic. The N-gain score calculation on pretest and posttest results showed medium and high learning improvement after online treatment. Similarly, online buffer solution learning achieved a good N-gain based on pretest and posttest. Based on data analysis of the five criteria met, online models in buffer solution material in class XI SMA Negeri 3 Kotamobagu are effective